1980
DOI: 10.1093/ajcn/33.5.1165
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Ascaris infection and growth of malnourished preschool children in Kenya

Abstract: A longitudinal study in Ascaris-infected and noninfected children was conducted in two Kenyan villages. Anthropometric, clinical, and stool exams were performed three times at 14-week intervals. All children received an anthelmintic drug (levamisole) at the second examination. In the 14 weeks before deworming, children with Ascaris (n = 61) did not differ from controls (n = 125) in percentage expected weight gain. In the 14 weeks after deworming, previously infected children showed higher percentage expected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(45 citation statements)
references
References 15 publications
3
40
0
2
Order By: Relevance
“…The negative impact of parasitic infections on growth is observed in many studies that use different measurements and indicators of anthropometric status, such as weight [15][16][17][18] , height [19][20][21] weight-forage 16,22 , height-for-age 16 and weight-forheight 17,[22][23][24] . For these authors, infections act negatively over the genetic growth potential of children and adolescents, keeping them from reaching full somatic growth.…”
Section: Discussionmentioning
confidence: 99%
“…The negative impact of parasitic infections on growth is observed in many studies that use different measurements and indicators of anthropometric status, such as weight [15][16][17][18] , height [19][20][21] weight-forage 16,22 , height-for-age 16 and weight-forheight 17,[22][23][24] . For these authors, infections act negatively over the genetic growth potential of children and adolescents, keeping them from reaching full somatic growth.…”
Section: Discussionmentioning
confidence: 99%
“…While Ascaris is most prevalent in areas of low socioeconomic status and thus poverty and malnutrition, studies indicate that Ascaris infection exerts a chronic influence on host nutrition [54]. Despite this, various intervention and clinical studies, the majority of which are focused on school children, demonstrated that infection is associated with appetite loss [55], lactose maldigestion [56] and impaired weight gain [55,57]. Age intensity profiles indicate that those harbouring heavy infections are young children at vulnerable stages of growth and development, and for this reason the impact of infection on nutritional status remains of primary concern and interest.…”
Section: Ascaris Associated Pathology and Morbiditymentioning
confidence: 99%
“…Similarly to human infection, porcine hosts display stunted growth and consume less food than uninfected controls [57,59].…”
Section: Ascaris Associated Pathology and Morbiditymentioning
confidence: 99%
See 1 more Smart Citation
“…Várias investigações demonstram que as condições nutricionais e a presença de parasitos intestinais em crianças, principalmente Ascaris lumbricoides, se correlacionam intensamente, uma vez que uma elevada carga parasitária no intestino pode ocasionar redução na entrada de nutrientes e absorção intestinal, aumento do catabolismo e sequestro de nutrientes requeridos para a síntese e crescimento tecidual. (FERREIRA et al, 1991;ANONYMOUS, 1983;STEPHENSON, 1980;MUNIZ-JUNQUEIRA;QUEIROZ;. Nossos resultados demonstraram que das 90 crianças com enteroparasitoses que foram hospitalizadas, 64 crianças encontravam-se com défi cit nutricional, fato que pode determinar a suscetibilidade à infecção por enteropasitoses.…”
Section: Materiais E Métodosunclassified